Does government spending reduce poverty in Nigeria? Evidence from Auto-Regressive Distributed Lag Specification. - Olufemi Samuel Adegboyo (e-Journal Ekonomi Bisnis dan Akuntansi, 2020)
This paper analyses the impact of government spending on poverty reducing in Nigeria for the period 1981 to 2017 making use of annual time series data. The study employs the Auto-Regressive Distributed Lag (ARDL) approach. The result of the study revealed that economic service recurrent expenditure (ESRX), social and community recurrent expenditure (SCSRX), Transfer recurrent expenditure (TRX) reduces poverty while transfer capital expenditure (TCX) and administrative recurrent expenditure (ADRX) escalate poverty. Consequently, the study recommends that Government should embark on provision of food subsidies, subsidies farm input for farmers, subsidies transportation cost. Furthermore, government should endeavor to pay pensioners all their entitlements including gratuities as at when due without any delay, government should also be giving stipend to the unemployed and disabled, more poverty alleviating programs should be organize Also, the huge cost of maintaining the government should be reduced by reducing the numbers of political appointees to a reasonable size.